(untitled) (Tanzania Medical Journal, 2022)
Background HIV infection causes a multisystem disease. Patients with upper gastrointestinal symptoms like dyspepsia, odynophagia, and dysphagia sometimes are usually treated empirically for esophageal candidiasis. Studies have suggested that a variety of other conditions may present with upper GIT and thus empirical treatment could potentially delay the institution of definitive treatment. This study describes endoscopic findings and prediction of esophageal candidiasis, which is an AIDS-defining illness among newly diagnosed people living with HIV at the Gastroenterology and hepatology unit at Bugando Tanzania. Methods A cross-section study was carried out among adult patients who presented at gastroenterology and hepatology unit for endoscopic service. All patients underwent HIV testing and counseling before the endoscope. Those who tested positive for HIV were serially enrolled in this study. Demographic, symptom profile, CD4 counts, and endoscopic findings were analyzed using STATA 13. The odds ratio (OR) with 95% Confidence Interval (CI) was calculated using univariate analysis followed by a multivariate analysis model to assess the extent of association. P value of <0.05 was considered as significant. Results In total 210 patients were enrolled in this study. The top three endoscopic findings were gastritis, 70 (33.3%; 95%CI: 26.9-39.7), esophageal candidiasis, 63 (30.0%; 95%CI: 23.8-36.2) and esophageal carcinoma, 28 (13.3%; 95%CI: 8.6-17.9). The presence of esophageal candidiasis was independently associated with Odynophagia, (OR: 6.1; 95%CI: 2.1-17.7; p=0.001), upper abdominal pain (OR: 2.3; 95%CI: 1.0-5.1, p=0.045) and CD4 count of less than 200cells/µL, (OR: 2.7; 95%CI: 1.3-5.3; p=0.005). Conclusion Esophageal candidiasis is prevalent in this study. Though Odynophagia, epigastric pains, and low CD4 counts can predict the presence of esophageal candidiasis, endoscopy is indicated for precise diagnosis of other conditions including esophageal carcinoma.